Deceptive desmas: molecular phylogenetics suggests a new classification and uncovers convergent evolution of lithistid demosponges. - Schuster, A.; Erpenbeck, D.; Pisera, A.; Hooper, J.; Bryce, M.; Fromont, J.; Wörheide, G. (PLOS One, 2015)
Reconciling the fossil record with molecular phylogenies to enhance the understanding of animal evolution is a challenging task, especially for taxa with a mostly poor fossil record, such as sponges (Porifera). ‘Lithistida’, a polyphyletic group of recent and fossil sponges, are an exception as they provide the richest fossil record among demosponges. Lithistids, currently encompassing 13 families, 41 genera and .300 recent species, are defined by the common possession of peculiar siliceous spicules (desmas) that characteristically form rigid articulated skeletons. Their phylogenetic relationships are to a large extent unresolved and there has been no (taxonomically) comprehensive analysis to formally reallocate lithistid taxa to their closest relatives. This study, based on the most comprehensive molecular and morphological investigation of ‘lithistid’ demosponges to date, corroborates some previous weakly-supported hypotheses, and provides novel insights into the evolutionary relationships of the previous ‘order Lithistida’. Based on molecular data (partial mtDNA CO1 and 28S rDNA sequences), we show that 8 out of 13 ‘Lithistida’ families belong to the order Astrophorida, whereas Scleritodermidae and Siphonidiidae form a separate monophyletic clade within Tetractinellida. Most lithistid astrophorids are dispersed between different clades of the Astrophorida and we propose to formally reallocate them, respectively. Corallistidae, Theonellidae and Phymatellidae are monophyletic, whereas the families Pleromidae and Scleritodermidae are polyphyletic. Family Desmanthidae is polyphyletic and groups within Halichondriidae – we formally propose a reallocation. The sister group relationship of the family Vetulinidae to Spongillida is confirmed and we propose here for the first time to include Vetulina into a new Order Sphaerocladina. Megascleres and microscleres possibly evolved and/or were lost several times independently in different ‘lithistid’ taxa, and microscleres might at least be four times more likely lost than megascleres. Desma spicules occasionally may have undergone secondary losses too. Our study provides a framework for further detailed investigations of this important demosponge group.